A Novel Approach to the Viability Determination of Mycobacterium avium subsp. paratuberculosis Using Platinum Compounds in Combination With Quantitative PCR - Cechova, Martina; Beinhauerova, Monika; Babak, Vladimir; Slana, Iva; Kralik, Petr (Frontiers in Microbiology, 2021)
Mycobacterium avium subsp. paratuberculosis (MAP) represents a slow-growing bacterium causing paratuberculosis, especially in domestic and wild ruminants. Until recently, the assessment of MAP viability relied mainly on cultivation, which is very time consuming and is unable to detect viable but non-culturable cells. Subsequently, viability PCR, a method combining sample treatment with the DNA-modifying agent ethidium monoazide (EMA) or propidium monoazide (PMA) and quantitative PCR (qPCR), was developed, enabling the selective detection of MAP cells with an intact cell membrane. However, this technology requires a laborious procedure involving the need to work in the dark and on ice. In our study, a method based on a combination of platinum compound treatment and qPCR, which does not require such a demanding procedure, was investigated to determine mycobacterial cell viability. The conditions of platinum compound treatment were optimized for the fast-growing mycobacterium M. smegmatis using live and heat-killed cells. The optimal conditions consisting of a single treatment with 100 μM cis-dichlorodiammine platinum(II) for 60 min at 5°C resulted in a difference in quantification cycle (Cq) values between live and dead membrane-compromised mycobacterial cells of about 6 Cq corresponding to about 2 log10 units. This optimized viability assay was eventually applied to MAP cells and demonstrated a better ability to distinguish between live and heat-killed mycobacteria as compared to PMA. The viability assay combining the Pt treatment with qPCR thereby proved to be a promising method for the enumeration of viable MAP cells in foodstuffs, environmental, and clinical samples which could replace the time-consuming cultivation or laborious procedures required when using PMA.